FUNCTIONAL OUTCOMES AFTER OPEN RELEASE OF GLUTEUS MAXIMUMS CONTRACTURE.: JPUMHS; 2025:15:01,158-166. http://doi.org/10.46536/jpumhs/2025/15.01.609 - Zubair Shah1, Abdullah2, Abid Rehman3, Nadeem Akbar4, Miqdad Hussain5, Asnaf Siddique6 , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2025)
BACKGROUND: Fibrosis and shortening of the gluteal muscles characterize gluteal Maximums contracture (GMC), a musculoskeletal disorder that causes limited hip motions and functional constraints such trouble squatting. It is frequently seen in adolescents and children, especially in underdeveloped areas. For moderate to severe instances, open surgical release is the usual course of therapy; however, there is currently little information available on the results of surgery in the local community. OBJECTIVE: To assess the functional outcomes of open surgical release in patients with gluteal muscle contracture treated at Khyber Teaching Hospital, Peshawar. METHODS: This retrospective cross-sectional research conducted in District Headquarters Hospital, Batkhela, from January to December of 2024. Included were 100 patients, 50 of whom were male and 50 of whom were female, ages 6 to 14, who had been diagnosed with gluteal muscle contracture and treated with open surgical release. Demographic information, contracture laterality, involvement type, and functional level were examined in clinical records. SPSS version 25 was used to analyze the data. To investigate correlations between gender, age, contracture type, and functional results, statistical techniques included one-way ANOVA, independent t-test, and chi-square test. RESULTS: Bilateral contracture was more prevalent in female patients (p = 0.043) out of 100 patients (50 males and 50 females), with a mean age of 9.36 ± 1.69 years. Age differences across contracture types were not statistically significant (p = 0.074). 58% of patients (n = 58) showed bilateral contractures, whereas 42% (n = 42) had unilateral involvement. Bilateral contracture was found in 58% of patients and unilateral in 42%. A significant association was noted between gender and contracture laterality (p = 0.043). Males were more likely than females to have unilateral engagement on the right side, although the difference was not statistically significant (p = 0.200). There was no significant difference in mean age between the bilateral and unilateral groups (p = 0.710). CONCLUSION: Open surgical release offers positive functional outcomes in children with GMC. Early surgical intervention improves mobility and quality of life.